The impact of foreign direct investment on regional economy: a Brazilian investigation - Carvalho, Ana Catarina Gandra de (Universidade Federal de São Carlos, 2023)
Regional Economic research shows that foreign direct investment (FDI) directly impacts the host region's economy. This debate is even more critical in emerging economies, where FDI has significant potential to increase and modernize domestic firms' capabilities. However, the effects of FDI on the regional economy still need to be fully explored, especially in Latin American countries. This study seeks to examine the impacts of FDI on the regional economy in Brazil, one of the largest recipients of foreign investment in Latin America. To this end, this research aims to examine 1) the state of the art of the literature that assesses the impact of FDI on domestic firms through a systematic literature review; 2) the impact of FDI on domestic firms at the regional level in Brazil; 3) the effects of FDI on economic complexity at the regional level. This study employed a unique FDI intensity dataset at the regional level. The results suggest that FDI has the potential to benefit the regional economy by increasing the number of jobs in domestic firms and increasing economic complexity. However, factors such as regional absorptive capacity and the input sector must be considered. FDI entry into regions with low absorption capacity has no positive effect on economic complexity. While FDI into high-tech sectors has a negative impact on job creation in domestic firms. The findings of this study contribute to the literature on the effects of FDI on the regional economy and have important implications for public policies concerning foreign investments. This study can, and must, be used to help the development of FDI related policies in Brazil and other Latin American countries. The use of results like those presented here is critical to directing foreign investment so that host regions can benefit from this type of investment.
O impacto do investimento estrangeiro direto na economia regional: uma investigação Brasileira
Keywords: Foreign direct investment (FDI); Regional economy; Crowd-in; Crowd out; Host firms; Economic complexity (EC); Absorptive capacity (AC); Systematic literature review (SLR); Panel data; Econometrics; Brazil; Brasil; Investimento Estrangeiro Direto (IED); Economia regional; Firmas domésticas; Capacidade de absorção; Complexidade econômica; Revisão sistemática da literatura (RSL); Dados em painel; Econometria; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA REGIONAL E URBANA::ECONOMIA REGIONAL; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA ECONOMICA